Electrocatalytic Activities of Platinum and Palladium Catalysts for Enhancement of Direct Formic Acid Fuel Cells: An Updated Progress - Zatil Amali Che Ramli; Jagadeesh Pasupuleti; Tengku Shafazila Tengku Saharuddin; Yusra Nadzirah Yusof; Wan Nor Roslam Wan Isahak; Luqmanulhakim Baharudin; Chong Tak Yaw; S.P. Koh; Sieh Tiong Kiong (Elsevier, 2024)
Indexed by WOS/Scopus/ERA